Increasing Possibilities of Nanosuspension - Kumar Bishwajit Sutradhar; Sabera Khatun; Irin Parven Luna (Journal of Nanotechnology)
Nowadays, a very large proportion of new drug candidates emerging from drug discovery programmes are water insoluble and thus poorly bioavailable. To avoid this problem, nanotechnology for drug delivery has gained much interest as a way to improve the solubility problems. Nano refers to particles size range of 1–1000 nm. The reduction of drug particles into the submicron range leads to a significant increase in the dissolution rate and therefore enhances bioavailability. Nanosuspensions are part of nanotechnology. This interacts with the body at subcellular (i.e., molecular) scales with a high degree of specificity and can be potentially translated into targeted cellular and tissue-specific clinical applications designed to achieve maximal therapeutic efficacy with minimal side effects. Production of drugs as nanosuspensions can be developed for drug delivery systems as an oral formulation and nonoral administration. Here, this review describes the methods of pharmaceutical nanosuspension production including advantages and disadvantages, potential benefits, characterization tests, and pharmaceutical applications in drug delivery.